SCLEROSING CHOLANGITIS - Martins, E; Chapman, R (1995)
Primary sclerosing cholangitis is a chronic cholestatic liver disease of unknown etiology that leads to progressive obliterative fibrosis of the biliary tree. It is strongly associated with ulcerative colitis. The disease progresses in most patients to death from liver failure or cholangiocarcinoma. Although the etiology remains unknown, it is clearly immune mediated, confirmed by the close association with the autoimmune haplotype HLA A1, B8, DR3, DR52a. In addition, in over 70% of cases, antineutrophil cytoplasmic antibody that does not disappear after liver transplantation circulates. The neutrophil antigen remains unknown. The gold standard for diagnosis remains endoscopic retrograde cholangiopancreatography. The clinical course is variable, and patients may be asymptomatic at presentation. Median survival ranges from 12 to 21 years. The diagnosis of cholangiocarcinoma in primary sclerosing cholangitis remains difficult to establish, although serum markers such as carcinoembryonic antigen and carbohydrate antigen CA 19-9, and histologic markers such as dysplasia may suggest the development of bile duct cancer. No medical treatment is of proven benefit, but ursodeoxycholic acid is the most promising therapy. Orthotopic liver transplantation remains the only effective treatment and the results are excellent, with a 5-year survival rate higher than 70%.